ANALISIS KARAKTERISTIK PARKIR DI RUMAH SAKIT PANTI RAHAYU “YAKKUM” PURWODADI GROBOGAN: ANALISIS KARAKTERISTIK PARKIR DI RUMAH SAKIT PANTI RAHAYU “YAKKUM” PURWODADI GROBOGAN - Mahardika, Vera; Setiawan, Dedi Budi; Pamungkas, Nur Setiaji; Wicaksono, Teguh Mulyo; Muldiyanto, Agus; Ardiansyah, Yogi; Yovanda, Dea Afa; Adhi, Dwi Respono (Politeknik Negeri Semarang, 2025)
Panti Rahayu “Yakkum” Hospital Purwodadi has provided three parking spaces that are still within the hospital complex. In the parking area, it is currently unknown what the characteristics of parking and how much parking space is needed. This study aims to determine the characteristics of parking, capacity, and the need for existing parking spaces. The research method used is the observation method and literature study. This study was conducted for 3 days, namely Saturday, Sunday, and Monday, starting at 08.00 – 20.00 (12 hours) with a recorded time interval of 15 minutes. The results obtained were 602 vehicles for the highest parking volume for motorcycles and 156 vehicles for cars, the highest parking accumulation for motorcycles was 469 vehicles and 120 vehicles for cars, the parking index for cars was 122.45%, while for motorcycles it was 87.99%, the average duration of parking for motorcycles and passenger cars was 2.5 hours/vehicle and for parking turnover it had the same parking turnover rate between motorcycles and cars, The parking capacity for motorcycles is 1 vehicle, while for cars it is 3 vehicles. The total capacity for motorcycles is 533 SRP, while the capacity for cars is 49 SRP. However, when viewed from the highest incoming vehicle volume, the parking capacity is insufficient to meet the parking needs of patients, visitors and hospital employees. Researchers recommend that Panti Rahayu “Yakkum” Hospital Purwodadi add parking space or build a multi-story building parking lot.